Saliva as a potential matrix for evaluating pharmacologically active dolutegravir concentration in plasma. - Eiko Yamada; Ritsuo Takagi; Hiroshi Moro; Koji Sudo; Shingo Kato (PLoS ONE, 2021)
Therapeutic drug monitoring (TDM) is used in certain clinically selected cases and in research settings to optimize the response to antiretroviral therapy. Plasma of blood is commonly used for TDM, but blood sampling is invasive and at risk for transmission of infectious agents. On the other hand, saliva sampling is noninvasive, safe, cheap, and easily performed compared to blood. Dolutegravir (DTG) is now widely prescribed as a key component of antiretroviral therapy for HIV infection. In this study, we examined the relationship between DTG concentrations in plasma and saliva of treated patients to explore the possibility of using saliva as an alternative body fluid of TDM. A total of 17 pairs of blood and saliva samples were obtained from 15 consented HIV-1-infected subjects treated with DTG containing regimens for more than one month. Both blood and saliva samples were collected within 1 h of each other. Drug concentrations were determined by liquid chromatography-tandem mass spectrometry using DTG-d5 as an internal standard. The LLOQ was 0.5 ng/mL. The calibration curves were prepared with pooled plasma or saliva containing DTG in a range of 0.5-100 ng/mL with precision of <14.4% and accuracy within ±14.7%. The DTG concentrations in the plasma and saliva were significantly correlated (Pearson's correlation coefficient r = 0.76, p < 0.001). The median ratio of the drug concentration in saliva to those in plasma was 0.0056, which is close to the rate of non-protein-bound DTG in plasma (0.70%), suggesting that only free DTG in plasma is transported to the salivary glands and secreted into saliva. The present study demonstrates that DTG concentration in saliva reflects the pharmacologically active drug concentration in plasma and may provide an easily accessible alternative for monitoring effective antiretroviral treatment.